(untitled) (SNPRC Journal, 2025)
This paper explores the perception and practice of menstrual activities of female students at the public campuses of Rupandehi district of Nepal. This study aimed to examine female students’ understanding of menstrual hygiene in public campuses. It also explores the social cultural beliefs related to the menstruation and their impact on educational activities. This study was quantitative research.120 female students of a public campus of Rupandehi district were selected as sample for the study. This study revealed diverse perspectives on mensuration. Majority 66% of respondents viewed as a natural process but it was found sociocultural beliefs and practices like restriction during mensuration vary among respondents. Mothers appeared as primary source of information about mensuration which underscores the important role of family in educating students about reproductive health. The study also revealed that the influence of family members in imposing restrictions during menstruation is obvious with many female students mentioned the whole family as the source of pressure. The study suggested the need to address menstrual hygiene as a critical factor in female students’ educational outcomes and to create supportive campus environments. It recommended targeted actions such as awareness programmes, access to hygiene sanitary products, proper disposal training and support services to improve students’ health behavior and well-being